Religion and faith-based welfare : from wellbeing to ways of being / Rana Jawad. - Jawad, Rana (Policy, 2012)
This original book offers a critical overview of the role of religious values, actors and institutions in the development of social welfare provision in Britain, combining historical discussion of the relationship between religion and social policy in Britain with a comparative theoretical discussion covering Europe and North America.